A mire of highly subjective and ineffective voluntary guidelines: tobacco industry efforts to thwart tobacco control in Malaysia. (24th November 2004) - Assunta, M; Chapman, S
Abstract : Objective: To describe tobacco industry efforts in Malaysia to thwart government efforts to regulate tobacco promotion and health warnings. Methods: Systematic keyword and opportunistic website searches of formerly private tobacco industry internal documents made available through the Master Settlement Agreement and secondary websites; relevant information from news articles and financial reports. Results: Commencing in the 1970s, the industry began to systematically thwart government tobacco control. Guidelines were successfully promoted in the place of legislation for over two decades. Even when the government succeeded in implementing regulations such as health warnings and advertising bans they were compromised and acted effectively to retard further progress for years to come. Conclusion: Counter-measures to delay or thwart government efforts to regulate tobacco were initiated by the industry. Though not unique to Malaysia, the main difference lies in the degree to which strategies were used to successfully counter stringent tobacco control measures between 1970 and 1995.